SINTESIS DAN KARAKTERISASI EDIBLE FILM BERBAHAN BAKU GELATIN HASIL ISOLASI KULIT CEKER AYAM BROILER - I Made Sutha Negara; I Nengah Simpen (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2014)
The research of synthesis and characterization of edible films base material on gelatin which is isolated from chiken feet skin of broiler has been carried out. The gelatin of isolation product as raw material to produce edible film, through determination of optimum condition with the study variaty concentrations of gelatin (%, m/v) such as 10%, 18%, and 20%, and variety concentrations of glycerol plastisizer (% m/v) such as 1.0%; 1.8%; and 2.0% or the ratio of gelatin and glycerol was 10:1. The edible films which produced was analyzed its quality, to determine characteristic of physico-chemical properties such as water content, solubility edible films in water and fuctional groups by infrared (FTIR). The gelatin without treatment (without mixture with glycerol) as control. The research showed that increasing glycerol (plastisizer) content can increase water content and solubility edible film in water, because glycerol properties which more easy to bond with water molecular so that good solubility in water. The analysis result of FTIR showed that the adition of glycerol can move absorption, generally increasing on amide A, amide II and amide III. The analysis result of LIBS showed that the intensity of atomic content such as C atom on wavelenght of 283, 426, and 723 nm, H atom on wavelenght of 434 and 484 nm, and O atom on wavelenght of 777 and 844 nm for edible films possess relative emission intensity higher then control. The edible films with gelatin and glycerol ratio 20:1.0 glycerol) indicate better properties (the best condition).